COPDCompEx: A novel composite endpoint for COPD exacerbations to enable faster clinical development. (November 2020) - Vogelmeier, Claus F.; Fuhlbrigge, Anne; Jauhiainen, Alexandra; Scheepers, Lieke E.J.M.; Bengtsson, Thomas; Peterson, Stefan; Karlsson, Niklas; Sethi, Tariq; Locantore, Nicholas; Tal-Singer, Ruth; Rennard, Stephen; Fagerås, Malin; et al.
Abstract: Background: Frequency of moderate and severe chronic obstructive pulmonary disease exacerbations is an important endpoint in clinical trials, but makes them large and lengthy when powered to evaluate it. We aimed to develop a composite endpoint (COPDCompEx) that could predict treatment effect on exacerbations, enabling the design of shorter early phase clinical trials requiring fewer patients. Methods: In this post hoc analysis, data from 20 randomized controlled trials were used to develop and test COPDCompEx. Diary events were tested against predefined threshold values for peak expiratory flow, reliever medication use, and symptoms. A COPDCompEx event was defined as first occurrence of a diary event, a moderate or severe exacerbation, or a study dropout. Ratios of event frequency, treatment effect and future trial sample size were compared between COPDCompEx and moderate and severe exacerbations. Findings: At 3 months, the proportion of patients experiencing COPDCompEx events increased over 3-fold versus exacerbations alone. All components contributed to COPDCompEx event rate. Treatment effects at 3 months were closely matched between COPDCompEx and exacerbations, and the large net gain in power substantially reduced the required sample size. Interpretation: COPDCompEx may be used to predict treatment effect on moderate and severe exacerbations of chronic obstructive pulmonary disease. This may enable the design of shorter Phase 2 clinical trials requiring fewer patients when compared with current exacerbation studies, with exacerbations as a key Phase 3 endpoint. This would, therefore, allow more efficient decision-making with reduced burden and risk to study participants. Highlights: COPDCompEx is a novel endpoint to measure treatment effects on COPD exacerbations. COPDCompEx 3-month treatment effect reflected that on exacerbations at 6–12 months. All components contributed to the COPDCompEx event rate. The enhanced power of COPDCompEx may facilitate shorter and smaller clinical trials. The value of including peak flow suggests its utility as an assessment tool in COPD.